Courses for Kids
Free study material
Offline Centres
Store Icon

How do you write $y + 9 = - 3(x - 2)$ in standard form?

Last updated date: 17th Jun 2024
Total views: 372.9k
Views today: 6.72k
372.9k+ views
Hint: Take out all the like terms to one side and all the alike terms to the other side. Take out all the common terms. Then substitute the value of the expression in the other equation. Reduce the terms on the both sides until they cannot be reduced any further if possible. Then finally evaluate the value of the unknown variable. Then convert the equation to the standard form which is given by $x + y = c$.

Complete step-by-step solution:
First we will start off by taking all the like terms to one side in the first equation.
\Rightarrow y + 9 = - 3(x - 2) \\
\Rightarrow y + 3(x - 2) = - 9 \\
Now we will open the brackets and reduce the terms on both the sides.
\Rightarrow y + 3(x - 2) = - 9 \\
\Rightarrow y + 3x - 6 = - 9 \\
\Rightarrow y + 3x = - 9 + 6 \\
\Rightarrow y + 3x = - 3 \\
Now we will convert the equation to its standard form.
\Rightarrow y + 3x = - 3 \\
 \Rightarrow x + \dfrac{y}{3} = - 1 \\
Hence, the equation $y + 9 = - 3(x - 2)$ in standard form is given by $x + \dfrac{y}{3} = - 1$.

Additional Information: To cross multiply terms, you will multiply the numerator in the first fraction times the denominator in the second fraction, then you write that number down. Then you multiply the numerator of the second fraction times the number in the denominator of your first fraction, and then you write that number down. By Cross multiplication of fractions, we get to know if two fractions are equal or which one is greater. This is especially useful when you are working with larger fractions that you are not sure how to reduce. Cross multiplication also helps us to solve for unknown variables in fractions.

Note: While taking terms from one side to another, make sure you are changing their respective signs as well. While opening any brackets, always multiply the signs present outside the brackets along with the terms. Reduce the terms using the factorisation method.